Interview with an Inuit Women Artists (1972)
Interview / [Unidentified Inuit women through an interpreter]. Item consists of an audio recording of an interview, through the aid of an interpreter, with two unidentified Inuit women whose artwork was chosen to be in a Roman Catholic mass book. The topics discussed in the first interview include the picture she drew, other spiritual art she has created, her religious/spiritual beliefs, and the recent strides the Catholic church has made to be inclusive towards Aboriginal peoples. The topics for the second interview include her print for the mass book, her thoughts on being asked to participate in artwork for the Roman Catholic church, Aboriginal food sharing rituals, her thoughts in choosing the theme of the picture, and her trip to the south. The audio cuts off abruptly. Item appears to be a continuation of a recording of a conversation on tape 1989-020 / 008 (50) (ASC33128). 2 tracks on mono at 3 3/4 ips. The recording cuts off abruptly. Digitization possible in part through a Young Canada Works (YCW) program funded through the Department of Canadian Heritage and managed by the Canadian Council of Archives (CCA).